2023
DOI: 10.1097/pg9.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of New-Onset Ulcerative Colitis Following Recent Diagnosis of COVID-19

Matthew D. Swatski,
Panamdeep Kaur,
Rachel E. Borlack
et al.

Abstract: There have been only 2 reported cases of new-onset ulcerative colitis in pediatrics following acute coronavirus disease 2019 (COVID-19). We are reporting a case series of 3 adolescent female patients, 2 of whom were vaccinated against COVID-19, who developed new-onset ulcerative colitis following a recent diagnosis of COVID-19 infections at a singular pediatric hospital. This case series should be an impetus to clinicians who have pediatric patients with persistent symptoms of hematochezia, diarrhea, and abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For instance, Kim et al [89] reported two cases of Crohn's disease in previously healthy male patients aged 17 and 11 years old. Swatski et al reported a case series of 2 female patients aged 16 years old and a female patient aged 12-years old with new-onset ulcerative colitis following a recent diagnosis of COVID-19 [90]. Although these cases seem to be rare, it is important to be aware of the need for further investigations into IBD in children with persistent hematochezia, diarrhea, and/or abdominal pain following COVID-19 [91,92].…”
Section: De Novo Pediatric Ibd Post Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Kim et al [89] reported two cases of Crohn's disease in previously healthy male patients aged 17 and 11 years old. Swatski et al reported a case series of 2 female patients aged 16 years old and a female patient aged 12-years old with new-onset ulcerative colitis following a recent diagnosis of COVID-19 [90]. Although these cases seem to be rare, it is important to be aware of the need for further investigations into IBD in children with persistent hematochezia, diarrhea, and/or abdominal pain following COVID-19 [91,92].…”
Section: De Novo Pediatric Ibd Post Covid-19mentioning
confidence: 99%
“…On a long-term basis, these patients might require close monitoring, as this pro-inflammatory state could persist through time and cause additional complications. COVID-19 vaccination status does not seem to have an influence on disease onset or evolution [89,90]. In the adult population, however, there are new cases of IBD with onset reported after a previous SARS-CoV-2 infection, most of them with severe evolution, reflecting another aspect of the intricate SARS-CoV-2-IBD relationship [97][98][99][100].…”
Section: De Novo Pediatric Ibd Post Covid-19mentioning
confidence: 99%